Association of Dyslipidemia and Glucose Abnormalities With Antiretroviral Treatment in a Cohort of HIV-Infected Latin American Children. (1st January 2017) - Paganella, Machline P.; Cohen, Rachel A.; Harris, Donald R.; de Souza Kuchenbecker, Ricardo; Sperhacke, Rosa D.; Kato, Sergio K.; Oliveira da Silva, Carmem L.; Sturzbecher, Fernanda T.; Oliveira, Ricardo H. S.; Pavía-Ruz, Noris; Hazra, Rohan; ,
Abstract : Objective: To estimate the incidence of lipid and glucose abnormalities and assess their association with exposure to antiretroviral (ARV) regimens among perinatally HIV-infected Latin American children. Design: Longitudinal cohort study. Methods: Data were analyzed from the Eunice Kennedy Shriver National Institute of Child Health and Human Development International Site Development Initiative Pediatric Latin American Countries Epidemiologic Study. The incidence of dyslipidemia [total cholesterol >200 mg/dL, HDL < 35 mg/dL, LDL ≥ 130 mg/dL, triglycerides > 110 mg/dL (age < 10 years) or >150 mg/dL (≥10 years)] and fasting glucose abnormalities [homeostasis model assessment of insulin resistance >2.5 (Tanner stage 1) or >4.0 (Tanner stage > 1); impaired glucose: 110 to <126 mg/dL; diabetes: ≥126 mg/dL] was estimated. Proportional hazards regression was used to evaluate the risk of abnormalities associated with ARV regimen, adjusted for covariates. Results: There were 385 children eligible for analysis (mean age 6.6 years). Incident cholesterol abnormalities were reported in 18.1% of participants [95% confidence interval (CI): 14.1% to 22.8%], HDL and LDL cholesterol abnormalities in 19.6% (15.1%–24.7%) and 15.0% (11.3%–19.5%), respectively, and triglyceride abnormalities in 44.2% (37.7%–50.8%). In multivariable analysis, ARV regimen was only associated with triglyceride abnormalities; participants receiving a protease inhibitor (PI)-containing regimen were 3.6 times as likely to experience a triglyceride abnormality as those receiving no ARVs (95% CI: 1.3 to 10.5; P = 0.0167). The cumulative incidence of insulin resistance was 3.8% (1.8%–7.1%); there were no incident cases of diabetes and only 2 of impaired fasting glucose. Conclusions: Children receiving PI-containing regimens were at increased risk of developing triglyceride abnormalities. Continued monitoring of lipid levels in children receiving PI-containing regimens appears warranted.